Tatak Pilipino [episode no. 47] ([Quezon City ABS-CBN], 1991)
A unique display of Pilipino ways and style.
Nakakagaling na mummy (5 min.) -- Embalming (5 min.) -- Pre-historic death and burial practices (15 min.) -- Art works of Jose Legaspi (5 min.) -- Cremation (10 min.) -- Aswang (10 min.) -- Chinese cemetery (10 min.) -- Kulam sa Siquijor (10 min.).
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Legaspi, Jose; Mummies -- Philippines; Cemeteries -- Philippines; Cremation -- Philippines; Embalming; Witchcraft -- Philippines -- Siquijor; Sociology; Fine arts